MAKING THE EQUIPMENT OF THE MODERN AMENITIES OF THE ECOLOGICAL TERMINOLOGY BY TEACHING COURSES «GENERAL ECOLOGY» AND «THE BASES OF ECOLOGY» - Зоріна, Н. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Here is given the methods of necessity in introduction the ecological terminology which is contained in over 30 textbooks and train aids on general ecology (and neoecology) and the bases of ecology, for synonymous its understanding by the students of higher educational establishments.